IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE PRINCIPLES IN VILLAGE FUND MANAGEMENT IN TENGGAK VILLAGE GOVERNMENT, SIDOHARJO, SRAGEN - Diego Wardana Putra; Mohammad Hasanudin; Alvianita Gunawan Putri (Dinamika Akuntansi Keuangan dan Perbankan, 2023)
This study aims to describe and analyze the principles of Good Corporate Governance in managing village funds at the Tenggak Village Government, Sidoharjo District, Sragen Regency. This type of research uses a descriptive method with a qualitative approach. This research design is considered as the most suitable application to explain the good governance principles in the Tenggak Village government in depth according to the actual phenomena. Data collection techniques carried out containe of interviews, observation and documentation. The results of this study indicate that the principles of responsibility, independence, and justice have been applied properly. Therefore the principle of transparency has not been applicated properly and the principle of accountability has not met the existing research indicators. The final result indicated that the principles of good corporate governance have not been implemented properly in village fund management in Tenggak village governance.